IMPLEMENTASI CYBER NOTARY DALAM RUPS ELEKTRONIK PADA PERSEROAN TERBUKA: ANALISIS BATASAN WEWENANG DAN PERLINDUNGAN HUKUM NOTARIS - Anis Khafifah Mz; Nuzulia Kumala Sari (CV. Lafadz Jaya, 2026)
The development of information technology has driven the transformation of the General Meeting of Shareholders (GMS) mechanism from face-to-face to electronic (e-GMS). This is intended to eliminate the constraints of distance and location between shareholders. This phenomenon places notaries in a crucial position as cyber notaries to ensure the authenticity and legal certainty of the minutes of meetings held online. The authority of notaries, expressly stated in the UUJN, still emphasizes conventional processes, while notaries are also required to adapt to developments in information technology. In addition, notaries are also required to apply the prudent notary principle, which requires notaries to act with integrity, honesty, and thoroughness in verifying the identity, competence, and accuracy of the parties' statements to prevent legal defects in authentic deeds. This study aims to analyze the implementation of the cyber notary concept in the implementation of e-GMS, identify the technical and legal obstacles faced by notaries, and evaluate legal protection for notaries in exercising their authority.